Branded - Walters, Eric, 1957- (Orca currents., 2010)
When the principal of his school decides that the students must wear uniforms, Ian learns that the manufacturer of the uniforms is on the top-ten list for human-rights violations. When he tells the principal this, all he gets is a reminder that the penalty for refusing to wear the uniforms is suspension.